Give Trust a Chance-A Model of Trust in the Context of an IMF-Supported Program - Sembene, Daouda (IMF Working Papers; Working Paper ;, 2007)
This paper is an attempt to identify the determinants of trust between country authorities and IMF staff in the context of an IMF-supported program. Using an outcomes-based definition of trust, a game-theoretic model is developed to compute the level of trust between the two parties. The results and the analysis of trust-related issues emerging in a program context suggest that trust between country authorities and IMF staff exerts a positive impact on the likelihood of program success through its ability to improve the quality of the design, the efficiency of negotiation, and the effectiveness of implementation of an IMF-supported program. Some initiatives to secure such benefits and enhance trust in staff are proposed.